Choice of Interceptor Aerodynamic Lifting Surface Location based on Autopilot Design Considerations - Sankar, Ram B.; Tiwari, P. K.; Bandyopadhyay, B.; Arya, H. (Defence Science Journal, 2021)
Interceptors operate at wide range of operating conditions in terms of Mach number, altitude and angle of attack. The aerodynamic design caters for such wide operating envelope by appropriate sizing of lifting and control surfaces for meeting the normal acceleration capability requirements. The wide range of operating conditions leads to an inevitable spread in center of pressure location and hence spread in static stability. The performance of control design is a strong function of the aerodynamic static stability. The total operating envelope can be bifurcated into statically stable and unstable zones and the aerodynamic lifting surface location can be used as a control parameter to identify the neutral stability point. During the homing phase lesser static stability is desirable for good speed of response, hence the lifting surface location needs to be chosen based on the capability of control to handle instability. This paper analyses the limitations of autopilot design for the control of an unstable interceptor and brings out a method to identify the optimum aerodynamic lifting surface location for efficiently managing static margin while satisfying the control limitations and homing phase performance. This provides an input on the most appropriate lifting surface location to the aerodynamic designer during the initial CFD based aerodynamic characterisation stage itself, before commencing the rigorous wind tunnel based characterisation.